Rectus sheath hematoma after abdominal trauma with snowball: A case report - Kayadibi, Yasemin; Tekcan Şanlı, Deniz Esin; Esmerer, Emel; Ors, Suna (Journal of Surgery and Medicine, 2019)
The rectus sheath hematoma (RSH) is the most common benign disease of the rectus abdominis muscle (RAM), but is one of the rare causes of acute abdominal pain. Mostly it is misdiagnosed with other causes of acute abdomen. A 65-year-old man admitted to our emergency service with complaints of localized abdominal pain and swelling after snowball playing and he had no anticoagulant drug history. He was diagnosed as RSH by computed tomography (CT) imaging. In elderly patient population, the clinician should be awake about RSH if the patient presented with local abdominal pain and infra abdominal mass. Early diagnosis by CT imaging is very important for exact diagnosis for prevention from unnecessary surgical procedures.